2013
DOI: 10.7567/apex.6.035602
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Phase Separation of a Mixed Film of a Photochromic Amorphous Molecular Material and a Quaternary Ammonium Salt

Abstract: Phase separation of the mixed film of an azobenzene-based photochromic amorphous molecular material, 4-[bis(9,9-dimethylfluoren-2-yl)amino]azobenzene, and a quaternary ammonium salt, tetrabutylammonium tetrafluoroborate, could be induced to form dissipative self-assembled microstructures not only by heating but also by photoirradiation. Fabrication of a micropattern and a relief grating composed of the quaternary ammonium salt by irradiation of the film followed by rinsing with hexane was demonstrated. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The results suggested that the main components of the circular domains and their periphery were TBABF 4 and TPTTA, respectively. It is notable that the diameter of the circular domain observed in the present study was almost similar to that for TBABF 4 -BFlAB system [12]. Therefore, the diameter of the circular domain was supposed to be determined irrespective of the kind of the amorphous molecular material.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results suggested that the main components of the circular domains and their periphery were TBABF 4 and TPTTA, respectively. It is notable that the diameter of the circular domain observed in the present study was almost similar to that for TBABF 4 -BFlAB system [12]. Therefore, the diameter of the circular domain was supposed to be determined irrespective of the kind of the amorphous molecular material.…”
Section: Resultssupporting
confidence: 81%
“…The extrapolation of the plots of the number density of circular domains vs. the concentration of the TBABF 4 suggests that the concentration of TBABF 4 in the peripheral phase was ca. 5 mol%, being larger than that for TBABF 4 -BFlAB system [12]. …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition to the above single component systems, we have also investigated photomechanical behaviors observed for binary systems. We have reported that the mixed film of 4-[bis(9,9-dimethylfluoren-2-yl)amino]azobenzene (BFlAB) and a quaternary ammonium salt exhibited photoinduced phase separation and that SRG composed of the quaternary salt could be obtained by interference irradiation of the mixed film followed by immersing to hexane [28]. In addition, we have reported the preliminary results of photomechanical effect observed for binary films of BFlAB and poly(vinyl acetate) (PVAc) obtained by spin-coating method [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we have recently started studies on photofunctional hybrid systems that include low molecular-mass component. For instance, hybrid films composed of azobenzene-based photochromic amorphous molecular materials, namely low molecular-mass photochromic materials that readily form amorphous glasses, and quaternary ammonium and phosphonium salts were found to exhibit phase separation to form dissipative self-assembled microstructures not only by heating but also by photoirradiation [6]. We have also found that hybrid films of azobenzenebased photochromic amorphous molecular materials and poly(vinyl acetate) (PVAc) exhibited thermally reversible phase-separation-dissolution transitions and that the structure of domains produced in the phase-separated film could be deformed by irradiation with polarized laser beam [7].…”
Section: Introductionmentioning
confidence: 99%